Experimental study on characteristics of the test engine fueled by biodiesel based Jatropha oil and traditional diesel - Nang Xuan Ho; Hoa Binh Pham; Vinh Nguyen Duy (AIMS Energy, 2020)
In this study, oil was converted to biodiesel via transesterification reaction under the presence of CaO at the laboratory. This aims to evaluate and compare the influence of Jatropha oil with commercial diesel (CD) fuel on the engine operating characteristics. Secondly, this study is to compare engine performance and temperature characteristics of cooling water and lubricant oil under various engine operating conditions of the test engine fueled by Jatropha oil and CD. The results indicated that the engine torque of the engine running with Jatropha oil dropped from 0.2 kW to 0.3 kW at all speeds and its brake specific fuel consumption (BSFC) increased at almost every speed due to the low heating value and high viscosity of the Jatropha fuel. The BTEs of the engines fuelled with Jatropha oil was 0.3%, 1.0%, 0.6%, 0.7%, 1.1%, 1.6%, and 1.0% smaller than the BTEs of the engine when varied speed from 1000 rpm to 2200 rpm. However, the difference was trivial. Also, Jatropha oil contributed to reducing the oil temperature of lubricant and cooling water.